Faktor Faktor Yang Mempengaruhi Purchase Intention Pada Brand Man Man Tang Di Batam - selly, Selly; Purba, Tiurniari (LPPM Universitas Putera Batam, 2021)
Brand awareness, perceived quality and electronic word of mouth can be a company marketing strategy over a product and forming a relationship between producers and concumers. This study aims to examine and analyze the influence of factor effecting purchase intention of brand Man Man Tang in Batam. By using purposive sampling obtained 130 respondents. Using multiple linear regression to data analysis and validity, reliability and classical assumption tests. this study proves that brand awareness perceived quality and electronic word of mouth affect purchase intentions both partially and simultaneously. From this study, it is expected that companies pay more attention to product quality and consumer reviews to increase purchase intention.